Distribution, occurrence mechanisms, and management of high fluoride levels in the water, sediment, and soil of Shahu Lake, China. (March 2021) - Tian, Linfeng; Zhu, Xiang; Wang, Longmian; Peng, Fuquan; Pang, Qingqing; He, Fei; Xu, Bin
Abstract: Fluoride (F − ) pollution is a serious global problem. However, relatively few studies have evaluated the occurrence mechanisms of F − from an entire lake system perspective and determined their major causes via quantitative analysis. This study analyzes the distribution and occurrence mechanisms of F − in the lake water, sediment, groundwater, and soil of Shahu Lake, as well as assessing the influence of the factors on the F − in the lake water via quantitative analysis. Our results show that the F − concentrations in groundwater are higher in the eastern area of the lake, which is different from that in the surface soil layer. The F − concentrations in the lake water vary from 0.95 to 1.40 mg/L, most of which exceed Chinese standards (1 mg/L). Groundwater F − concentrations at 35% of the sampling sites exceed 1 mg/L. The total F − in the soil is significantly higher than the global mean. Ca 2+ -deficiency (which is mainly accelerated by cation exchange between Ca 2+ and Na + ) together with alkaline water conditions and intense evaporation are the major contributors of F − enrichment in groundwater. The groundwater hydrochemistry is suitable for the dissolution of F − -bearing minerals. The F − in soil is not easily leached into groundwater. Approximately 6.96 t of F − is deposited into Shahu Lake annually, where 79.17% of the F − originates from water recharge. Evaporation is the main direct cause of high F − concentrations in the lake, whereas water recharge and obstructed surface water exchange are indirect causes. To effectively decrease the F − concentrations in the lake water, water exchange within the Shahu Lake system should be enhanced, or at least 4.42 million m 3 of lake water should be pumped out of the system before anthropogenic water recharge, with identically increasing volumes. Graphical abstract: Image 1 Highlights: Groundwater F − in eastern lake is higher than other areas, where soil F − is lower. Groundwater F − concentrations mainly derive from evaporation, not soil leaching. Exchange between Ca 2+ and Na + leads to high groundwater F − concentrations. Lake F − level is caused by direct evaporation and indirect water recharge. Pumping 4.42 million m 3 of water before water recharge inhibits increasing lake F − .